Viralnya Kampanye “All Eyes on Papua” Terindikasi FoMO - Buana Dewi, Asti Nur (Innovative: Journal Of Social Science Research, 2024)
The success of the “All Eyes on Rafah” campaign which went viral globally, sparked mass movements in various places in Asia, Europe, and America. On the other hand, in Indonesia, a campaign emerged that accompanied the momentum of “All Eyes on Rafah”, namely the “All Eyes on Papua” campaign. The “All Eyes on Papua” campaign started from a hashtag on social media X which was then shared on Instagram using the “Add Yours” feature and went viral in Indonesia. “All Eyes on Papua” which has been around since May 2024 made researchers want to know how the public received the message contained in the campaign. Did the “All Eyes on Papua” campaign spark the same mass movement as the “All Eyes on Rafah” campaign or did it just stop on social media as a FoMO trend? This research was conducted using a descriptive qualitative method and took data sources from literature and informant interviews. The conclusion obtained is that the “All Eyes on Papua” campaign, until the researcher wrote this journal report, was still just a campaign that stopped on social media as a FoMO trend.